Standardizing Academic Writing Proficiency: A Framework for Addressing Social Media Slang Exposure Among Digital Native Learners: A Literature Review - Caren Bernadeth F. Francisco (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
A critical gap in Philippine education research examines how exposure to social media slang impacts the academic writing proficiency of digital native learners—an issue particularly relevant to local learners who grow up using digital platforms as their primary means of daily communication. It focuses on four key dimensions: distinguishing formal and informal language registers, maintaining lexical precision, following standard syntactic structure, and the unintended transfer of informal digital language into formal academic work. The study employs a systematic literature review covering peer‑reviewed research, supplemented by empirical investigation. Findings show that frequent exposure leads to the unconscious carryover of slang, abbreviations, and shorthand into academic writing, resulting in register confusion, reduced vocabulary accuracy, and grammatical inconsistencies. While social media can boost general language engagement, it creates significant challenges for adhering to standard academic conventions. Drawing on language transfer theory, this work develops a pedagogical framework tailored to the Philippine K‑12 context, filling the absence of locally adapted, systematic interventions to support learners in navigating digital language habits and formal writing requirements.